An application of AHP in prioritizing critical factors of coal-based power generation: a case of Bangladesh - Zaman, Rafia; Islam, Nazrul; Kumar, Sivanappan; Bidir, Yuosre; Zimmermann, Willi; Asian Development Bank; Japan Scholarship Program (Pathumthani : Asian Institute of Technology, 2016)
As a low-cost primary fuel, coal is dominating global power generation portfolio accounting for 40.4% of global electricity in which developing economies are the main stakeholders. Coal remains the leading fossil fuel in the energy structure of the developing economies due to its positive association with economic development. However, coal-based power generation has become a major threat to carbon mitigation policy in global climate change context. Coal based power generation is heavily registered for {u1D436}{u1D442}2 emission representing 43% of total atmospheric GHG emission. Besides, other toxic air pollutants, emitted from coal power plants, have adverse impact on local environment as well as local community. These long-term socio-environmental liabilities make generation investment in coal power projects more indecisive. On the other hand, the emerging economies tend to depend heavily on coal combustion in their energy mix because of its relative price advantage and supply security compared to other fossil fuels. And, it will be challenging for those economies to have a right balance between economic development and negative externalities of coal power generation. This study is focused on identifying the critical factors of large-scale coal based power generation and prioritizing those factors using AHP technique. The study has considered the case of Bangladesh which is going to adopt 50% coal-based power generation policy by 2030. Bangladesh, world{u2019}s least energy consuming economy, is experiencing acute shortage in electricity supply due to depleting domestic natural gas reserves. Bangladesh is also regarded as next generation frontier economy due to its stable macroeconomic fronts. Hence, government tends to implement low-cost coal-based electricity production to achieve 100% electrification rate and to register into middle-income status economy. And, the issue of embracing coal power is highly being criticized and contested by the civic society of the country.
Based on extensive literature findings and expert opinions, the study identified 6 different dimensions of coal-based power generation including: coal sourcing (local and import), sector regulations and institutional settings, technological aspects in coal power plants, social risks and financing aspects (local and import based), health and safety (coal mining and coal power plants) and environmental degradation (coal mining and coal power plants). A set of 29 critical factors of coal-based power generation from these 6 dimensions were identified. To prioritize the critical factors, the study conducted expert interviews in Bangladesh. Total 18 energy experts provided their judgments for all critical factors and dimensions in a pair-wise comparisons fashion based on AHP technique. The critical factors were then ranked based on overall priorities in AHP and were grouped into 5 clusters using K-mean clustering. The analysis suggested that top two clusters are significantly important in addressing critical factors of coal-based power generation. The topmost critical cluster includes factors: public acceptance for coal power plants in locality, investment in coal power plants. The immediate next critical cluster include a number of factors namely, adequate legal instruments in local coal mining, development of logistical infrastructure for imported coal, human displacement and resettlement for local coal extraction and community health hazards. Also, air pollution, loss in agricultural productivity, pollution of water resources and so on belong to 3rd critical cluster.
A research submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, School of Management
Research Studies Project Report (M.BA.) - Asian Institute of Technology, 2016
Keywords: Application software; Coal; AHP (Computer programs)